The Evolving Reduction of Vancomycin and Daptomycin Susceptibility in MRSA-Salvaging the Gold Standards with Combination Therapy - Taylor Morrisette; Sara Alosaimy; Jacinda C. Abdul-Mutakabbir; Razieh Kebriaei; Michael J. Rybak (MDPI AG, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is associated with substantial morbidity and mortality. Vancomycin (VAN) has been used as the gold standard treatment for invasive MRSA infections for decades but, unfortunately, the reliance of VAN as the primary treatment option against these infections has led to a reduction in VAN susceptibility in MRSA isolates. Although daptomycin (DAP) is another common treatment option against invasive MRSA infections, it has been shown that the development of VAN resistance can lead to DAP nonsusceptibility. VAN or DAP backbone regimens in combination with other antibiotics has been advocated as an alternative approach to improve patient outcomes in VAN/DAP-susceptible infections, enhance outcomes in infections caused by isolates with reduced VAN/DAP susceptibility, and/or prevent the emergence of VAN/DAP resistance or further resistance. A peer-reviewed literature search was conducted using Medline, Google Scholar and PubMed databases. The primary purpose of this review is to describe the mechanisms and epidemiology of MRSA isolates with a reduction in VAN and/or DAP susceptibility, evaluate in vitro and in vivo literature describing combination therapy (CT) against MRSA isolates with reduced VAN and/or DAP susceptibility and describe studies involving the clinical outcomes of patients treated with CT against invasive MRSA infections.